Hafez in Love : A Novel - Pizishkzād, Īraj (Book collections on Project MUSE., 2020)
""Hafez in Love" is a historical novel centered around Iran's most beloved and best known poet, Shams al-Din Mohammad Hafez, and the city in which he lived"--